2020
DOI: 10.1542/peds.2019-1450
|View full text |Cite
|
Sign up to set email alerts
|

Cognition After Early Tonsillectomy for Mild OSA

Abstract: OBJECTIVES: It remains uncertain whether treatment with adenotonsillectomy for obstructive sleep apnea in children improves cognitive function. The Preschool Obstructive Sleep Apnea Tonsillectomy and Adenoidectomy study was a prospective randomized controlled study in which researchers evaluated outcomes 12 months after adenotonsillectomy compared with no surgery in preschool children symptomatic for obstructive sleep apnea.METHODS: A total of 190 children (age 3-5 years) were randomly assigned to early adenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 27 publications
6
50
0
Order By: Relevance
“…13 Global IQ as assessed by the Woodcock Johnson III Brief Intellectual Ability did not show significant gain at 12-month follow-up in children aged 3-5 years who underwent AT versus those without intervention. 13 A possible explanation for the negative finding was that the participants did not exhibit neurocognitive deficits at baseline when compared to age-appropriate norms, which was also demonstrated in a previous crosssectional study comparing preschoolers with and without OSA. 33 A similar floor effect may also explain the negative findings obtained from our current study.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…13 Global IQ as assessed by the Woodcock Johnson III Brief Intellectual Ability did not show significant gain at 12-month follow-up in children aged 3-5 years who underwent AT versus those without intervention. 13 A possible explanation for the negative finding was that the participants did not exhibit neurocognitive deficits at baseline when compared to age-appropriate norms, which was also demonstrated in a previous crosssectional study comparing preschoolers with and without OSA. 33 A similar floor effect may also explain the negative findings obtained from our current study.…”
Section: Discussionmentioning
confidence: 75%
“…14 However, nearly all published studies included children across all categories of severity and only two studies focused on mild disease. 13,15 One of them is a retrospective review which found that AT leads to a significant improvement in apnoea-hypopnoea index (AHI) on follow-up. 15 The other one is a recently published randomized controlled study which demonstrated an improvement in AHI accompanied by an improvement in behaviour but not cognitive function after AT in preschoolers.…”
Section: Introductionmentioning
confidence: 99%
“…Since OSA has been known to cause memory, learning and scholastic issues 7 often of different severity, diagnostic code classification is difficult. Furthermore, the 2 major end points used by the CHAT and POSTA trials were behavioural/functional and executive functioning 8,9 1).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the 2 major end points used by the CHAT and POSTA trials were behavioural/functional and executive functioning. 8,9 Therefore, we utilised those codes which were most associated with OSA after exclusion criteria were applied (Table 1).…”
mentioning
confidence: 99%
“…However, there appears to be greater improvements after surgery in less subjective measures as well: teacher-reported behaviour in the Childhood Adenotonsillectomy Trial (CHAT) 6 and persistence of daytime napping (a potential measure of daytime sleepiness in very young children) in the Preschool Obstructive Sleep Apnoea Tonsillectomy and Adenoidectomy (POSTA) study. 10 The unknown duration of, and likely inter-individual variability in, recovery of cognitive and behavioural functioning after the treatment of OSA also confounds our understanding of optimal treatment in this condition. The duration of follow-up in the randomized trials has been 6-12 months, 6,7,9,10 whereas there is reason to think that improvements in cognitive function may take longer than that.…”
mentioning
confidence: 99%